Efficacy of pipeline embolization device vs. traditional coils in embolization of intracranial aneurysms: A systematic review and meta-analysis - Li, Wei; Xiao, Zaixing; Zhao, Kaixuan; Yang, Shijie; Zhang, Yichuan; Li, Bin; Zhou, Yu; Ma, Yong; Chai, Erqing (Frontiers in Neurology, 2022)
Introduction In recent years, the Pipeline embolization device (PED) has been widely used in the embolization of intracranial aneurysms, but there are some inconsistent findings on whether its efficacy and safety are superior to those of traditional coils embolization (coils alone, stent-assisted coils and balloon-assisted coils). The purpose of this meta-analysis was to evaluate the safety and efficacy of PED in intracranial aneurysm embolization by comparing with traditional coils. Methods We systematically searched PubMed, Embase, Web of Science, and The Cochrane Library databases for randomized controlled trials and observational studies (case-control studies and cohort studies) comparing the efficacy of PED with traditional coils in intracranial aneurysm embolization published before April 1, 2022. The endpoints observed in this meta-analysis were procedure-related intracranial hemorrhage, procedure-related intracranial ischemia, other procedure-related complications (e.g., aneurysm rupture, neurological impairment, etc.), retreatment rate, complete occlusion (100%) of the aneurysm at the last follow-up, and favorable functional outcome (MRS ≤ 2). Results A total of 10 studies with a total of 1,400 patients (PED group: 576 and Traditional coils: 824) were included in this meta-analysis. A comprehensive analysis of the included literature showed that the PED group had a higher rate of complete aneurysm occlusion [OR = 2.62, 95% Cl (1.94, 3.55), p < 0.00001] and Lower re-treatment rate [OR = 0.20, 95% Cl (0.12, 0.34 p < 0.00001)] compared with the traditional coil embolization group at the last follow-up. In terms of procedure-related intracranial hemorrhage [OR = 3.04, 95% Cl (1.08, 8.57), p = 0.04] and other procedure-related complications [OR = 2.91, 95% Cl (1.48, 5.57), p = 0.002], the incidence of PED was higher than that of the traditional coil embolization group. Moreover, in terms of favorable functional outcome [OR = 0.4, 95% Cl (0.22, 0.71), p = 0.002] of patients at the last follow-up, the PED group was lower than the traditional coil embolization group. There was no statistically significant between the two groups in terms of surgery-related intracranial ischemia complications [OR = 0.88, 95% Cl (0.47, 1.64), p = 0.68]. Conclusion PED had higher rates of complete aneurysm occlusion and lower rates of aneurysm retreatment compared with traditional coils, but traditional coils was superior to the PED group in terms of procedure-related intracranial hemorrhage complication and other procedure-related complications (aneurysm rupture, neurological impairment), and favorable functional outcome (mRS ≤ 2). This result still needs to be further confirmed by additional large-sample, multicenter, prospective randomized controlled trials. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022325673.